2022
DOI: 10.17826/cumj.1093970
|View full text |Cite
|
Sign up to set email alerts
|

Otoprotective effects of farnesene against oxidative damage induced by paclitaxel

Abstract: Amaç: Bu çalışmanın amacı, güçlü serbest radikal süpürücü ve antioksidan özelliklere sahip farnesenin paklitaksel kaynaklı ototoksisite üzerindeki etkilerini biyokimyasal ve fonksiyonel yönden araştırmaktır. Gereç ve Yöntem: On sekiz erkek Wistar albino sıçan, altı sıçandan oluşan üç gruba rastgele ayrıldı. Araştırma boyunca kontrol grubuna paklitaksel veya farnesen verilmedi. Paklitaksel grubuna, 5mg/kg paklitaksel intraperitoneal olarak dört kez (1., 7., 14. ve 21. günlerde) verildi. Farnesen + paklitaksel g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…A few clinical trials on the impact of paclitaxel on sensorineural hearing loss have been documented [20,21]. Research revealing the link between hearing loss and paclitaxel, particularly in recent experimental studies, is notable and it is observed that paclitaxel reduces DPOAE frequencies [4,5,22]. Consistent with these results, a decline in DPOAE results was observed in the PCX group in the current research.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…A few clinical trials on the impact of paclitaxel on sensorineural hearing loss have been documented [20,21]. Research revealing the link between hearing loss and paclitaxel, particularly in recent experimental studies, is notable and it is observed that paclitaxel reduces DPOAE frequencies [4,5,22]. Consistent with these results, a decline in DPOAE results was observed in the PCX group in the current research.…”
Section: Discussionsupporting
confidence: 86%
“…In this context, diminishing the excessive ROS generation that underlies the pathophysiology of ototoxicity or boosting the antioxidant system can reduce the ototoxic effect of chemotherapeutics. Exogenous antioxidants are thus the most remarkable agents and have evolved into the main strategy of ototoxicity treatment in research [5,22,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations